Perturbation Theory of Operator Equations in the FréChet and Hilbert Spaces - Boichuk О. A.; Pokutnyi О. О. (Ukrains’kyi Matematychnyi Zhurnal, 2015)
The perturbation theory is constructed in the Fréchet and Hilbert spaces. An iterative process is proposed for finding branching solutions.